Green Pesantren-Based Entrepreneurship as an Alternative Educational Financing Strategy: Kewirausahaan pesantren berbasis lingkungan sebagai strategi alternatif pembiayaan pendidikan - Ummi Hani; Abdullah; Achmad Qusyairi Mahfudi (Mapendis: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to explore how green pesantren–based entrepreneurship functions as an alternative educational financing strategy in Islamic boarding schools. The research addresses the problem of financial sustainability in Islamic educational institutions, which often rely heavily on conventional funding sources and are vulnerable to economic instability. Using a qualitative case study approach, the research was conducted at Pondok Pesantren Nurul Jadid. Data were collected through in-depth interviews with institutional managers and business unit leaders, participant observation, and document analysis. The data were analysed using an interactive model consisting of data condensation, data display, and conclusion drawing. The findings reveal that environmentally oriented institutional programs, initially implemented as environmental awareness initiatives, have gradually evolved into structured entrepreneurial activities that generate additional funding for the pesantren. These programs are managed within the institutional framework, ensuring alignment with educational values and the pesantren's religious mission. The study demonstrates that green entrepreneurship can strengthen financial resilience without leading to the commercialisation of education. This research contributes to the discourse on Islamic education by offering a context-based model of sustainable educational financing that integrates environmental management, institutional entrepreneurship, and religious values.